Travels with a Small-town Librarian: Reflections from Coast to Coast - Wilson-Powell, Shelby (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2023)
A rural public library acts like a community hub just like its urban counterpart. In many ways, both offer the same services to their regional clientele. However, the methods those services are delivered need to uniquely adapt to the small community it services. As a Library and Information Science (LIS) professional, the rural library requires patience and understanding in order to mesh together formal education and realistic practices. From adjusting collection development goals to managing unionized staff, your degree cannot prepare you for everything. The experiences gained from this hands-on learning is unforgettable and incredibly rewarding for a young professional.